Pengaruh Penerimaan Pajak Daerah dan Zakat Terhadap Tingkat Kemiskinan di Indonesia Periode 2014-2022 - Shafarani, Yusri; Djatnika, Djoni; Mauluddi, Hasbi Assidiki; Laksana, Banter (Journal of Applied Islamic Economics and Finance, 2023)
Regional taxes and zakat are sources of state revenue that contribute significantly to overcoming the problem of poverty in Indonesia. This study aims to find out how the influence of the realization of regional tax and zakat revenues on the level of poverty in Indonesia. This study uses documentation methods, quantitative approaches, panel data regression analysis techniques, and secondary data sourced from provincial scale BAZNAS and LAZNAS, SIKD DJPK, and BPS. Data on the realization of regional tax and zakat revenues were obtained through a purposive sampling technique and obtained unbalanced panel data of 83 samples from 17 provinces in Indonesia during the 2014-2022 period. The results of this study indicate that partially, regional tax revenues have a negative and significant effect, while zakat receipts have a positive and insignificant effect on the poverty rate in Indonesia. Simultaneously, local tax and zakat revenues affect the level of poverty in Indonesia